LEGAL REQUIREMENTS FOR TEACHERS' ACTION IN THE EARLY YEARS OF FUNDAMENTAL EDUCATION (1996-2019) - Suficier, Darbi Masson [UNESP]; Marsico Azadinho, Mariana Passafaro; Muzzeti, Luci Regina [UNESP] (Unesp-faculdade Ciencias & Letras, 2020)
The aim of this article is to present, in chronological form, the changes in the formative requirements for the performance of teachers in the early years of elementary education, comprised in the legislation after the enactment of Law no. 9,394/1996. It becomes evident that the demand for higher education to work at this level of education is eased and relativized over time, maintaining the admissibility of the formation in the Normal School/Teacher-training colleges. Thus, the current guidelines for teacher-formation in the early years of elementary school are similar to those present in the LDB, promulgated more than two decades ago.
Keywords: Teacher-formation for the early years of fundamental education; Education legislation; Pedagogy; Normal School; Teacher formation colleges